DGM 430 OFFSET WEB MACHINE PRINT QUALITY - Maulana Ibrahim; Anton Hadiwibowo; Mukhyidin Djaiz; Henra Nanang Sukma (Kreator, 2019)
The review control activity, especially the decrease in the quality of the printed output, is one of the quality control parameters carried out by each company. To get quality, of course, the company does not remain silent, there are several things that need to be done or provided by the company to be able to support quality, namely man (human), machine (machine), material (material), and methods (methods). In the development of technology in an increasingly advanced digital world, companies want to continue to compete with a digital world by making breakthroughs, this of course makes the products produced by the company have a good or good quality level. In this study, there is an identification of the problem aspects that arise from the causes of the print results and how to get solutions to overcome the problems and factors that affect the quality of the print on the printed contents of the Cultural Arts Service Book using the DGM 430 Web Offset machineKeywords— Quality, Parameters, Web Offsets